Slowing down of adult body mass index trend increases in England: a latent class analysis of cross-sectional surveys (1992–2010) - Sperrin, M; Marshall, A D; Higgins, V; Buchan, I E; Renehan, A G (International Journal of Obesity, 2014)
Background: The prevalence of excess body weight, commonly measured as body mass index (BMI)⩾25 kg m −2 , has increased substantially in many populations worldwide over the past three decades, but the rate of increase has slowed down in some western populations. Objective: We address the hypothesis that the slowing down of BMI trend increases in England reflects a majority sub-population resistant to further BMI elevation. Design: Pseudo-panel data derived from annual cross-sectional surveys, the Health Surveys for England (1992–2010). Trends in median BMI values were explored using regression models with splines, and gender-specific mixture model (latent class analysis) were fit to take an account of increasing BMI distribution variance with time and identify hidden subgroups within the population. Subjects: BMI was available for 164 155 adults (men: 76 382; women: 87 773). Results: Until 2001, the age-adjusted yearly increases in median BMI were 0.140 and 0.139 kg m −2 for men and women, respectively, decreasing thereafter to 0.073 and 0.055 kg m −2 (differences between time periods, both P -values<0.0001). The mixture model identified two components—a normal BMI and a high BMI sub-population—the proportions for the latter were 23.5% in men and 33.7% in women. The remaining normal BMI populations were ‘resistant’ with minimal increases in mean BMI values over time. By age, mean BMI values in the normal BMI sub-population increased greatest between 20 and 34 years for men; for women, the increases were similar throughout age groups (slope differences, P <0.0001). Conclusion: In England, recent slowing down of adult BMI trend increases can be explained by two sub-populations—a high BMI sub-population getting ‘fatter’ and a majority ‘resistant’ normal BMI sub-population. These findings support a targeted, rather than a population-wide, policy to tackle the determinants of obesity.